2019
DOI: 10.1002/ceat.201800401
|View full text |Cite
|
Sign up to set email alerts
|

Activated Carbon‐Supported Mo‐Co‐K Sulfide Catalysts for Synthesizing Higher Alcohols from CO2

Abstract: Activated carbon-supported Mo-Co-K sulfide catalysts, prepared by stepwise impregnation, were used in the synthesis of higher alcohols via CO 2 hydrogenation. The catalysts with varying Mo contents and defined K/Mo and Co/Mo molar ratios exhibited relatively high CO 2 conversions and high selectivity to total alcohols and C 2+ alcohols. Moreover, the influence of calcination conditions on the sulfidation states and catalytic performance was studied. The surface sulfur runoff of the supported catalysts can be e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…The addition of KCl was found to increase the rate of alcohol and hydrocarbon formation from 26.4 to 34.1 × 10 − 2 mmol g cat − 1 h − 1 (carbon-based) with the selectivity to C 2+ alcohols (CO free) increasing from 2.8 % to 64.9 %. Furthermore, the positive effects of K as promoter were also observed for Co-Mo oxide and Co-Mo sulfide systems [142,143,162]. The addition of K to β-CoMoO 4 and α-CoMoO 4 by mechanically mixing led to a decrease in CO 2 conversion, though enhanced production of alcohols together with a higher ethanol selectivity (CO free) compared to catalyst without K addition (Fig.…”
Section: Effects Of Alkali Metals On the Performance Of Mo-based Catalystsmentioning
confidence: 64%
See 2 more Smart Citations
“…The addition of KCl was found to increase the rate of alcohol and hydrocarbon formation from 26.4 to 34.1 × 10 − 2 mmol g cat − 1 h − 1 (carbon-based) with the selectivity to C 2+ alcohols (CO free) increasing from 2.8 % to 64.9 %. Furthermore, the positive effects of K as promoter were also observed for Co-Mo oxide and Co-Mo sulfide systems [142,143,162]. The addition of K to β-CoMoO 4 and α-CoMoO 4 by mechanically mixing led to a decrease in CO 2 conversion, though enhanced production of alcohols together with a higher ethanol selectivity (CO free) compared to catalyst without K addition (Fig.…”
Section: Effects Of Alkali Metals On the Performance Of Mo-based Catalystsmentioning
confidence: 64%
“…At these conditions, relatively high selectivity to methanol (about 53 %) and ethanol (16 %) was obtained. Additionally, MoS 2 /AC mainly produced CO and hydrocarbons with a low amount of C 2+ alcohols [142]. Thus, it can be concluded that Mo-based materials alone are not efficient for HAS.…”
Section: Monometallic Mo-based Catalystsmentioning
confidence: 94%
See 1 more Smart Citation
“…Pt-Co 3 O 4 , FeRh-based catalysts, CoMo oxides and sulfides, and mixed CuFeZn oxides are only a few examples. [27][28][29][30][31][32][33][34][35][36][37] Their ability to combine rWGS (reverse water-gas shift) and FTS drives the hydrogenation of CO 2 into C 2 + alcohols. The FT functionality does not only enable chain growth but also competes with ethanol synthesis by producing C 2 + hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%
“…When it comes to classical heterogeneous catalysts, the best performing C 2+ alcohol synthesis catalysts are typically composed of first row transition metal oxides/sulfides or supported noble metals. Pt‐Co 3 O 4 , FeRh‐based catalysts, CoMo oxides and sulfides, and mixed CuFeZn oxides are only a few examples [27–37] . Their ability to combine rWGS (reverse water‐gas shift) and FTS drives the hydrogenation of CO 2 into C 2+ alcohols.…”
Section: Introductionmentioning
confidence: 99%